Signs & symbols - Dennis-Bryan, Kim; Hodgson, Nicola; Lockley, Neil (London New York DK Pub, 2008)
From simple shapes and colors to gods, mythical beasts, sacred rituals, and global branding, over 2,000 signs and symbols are explained through text, illustrations, and photography. Grouped thematically and comprehensively cross-referenced. Includes the physical world, animals, plants, humans, colors, shapes, patterns, numbers, picture writing, alphabets, international signs, professional signs, brands and logos, heraldic emblems, national flags, sign languages and signals, and symbolic gestures
The cosmos -- Natural world -- Human life -- Myths & religions -- Society & culture -- Symbol systems
"An illustrated guide to their origins and meanings"--Cover
Includes bibliographical references (p. 344-345) and index
1
Keywords: Signs and symbols -- History; Signs and symbols -- Mythology; Signs and symbols